Avaliação do potencial antitumoral in vitro de derivados glicosídicos de lapachol - Oliveira, Cristiane Almeida Santos (2024)
Lung cancer is the most lethal type of cancer worldwide, accounting for about 18% of deaths caused by the disease and ranking as the second most common cancer globally. Chemotherapy is a primary treatment in advanced stages of lung cancer; however, the drugs used may not be effective in severe cases and can have various adverse effects. Lapachol is a natural compound found in various plant species, showing cytotoxic effects on different tumor cell lines and holding great potential in treating the disease. Therefore, Lapachol has been used as an excellent source for creating synthetic derivatives to enhance its cytotoxic effects. In this study, we aimed to evaluate the cytotoxic activity of synthetic lapachol derivatives on lung carcinoma (A549), melanoma (B16F10), and glioma (C6) cell lines. Six lapachol derivatives were tested for their inhibitory capacity using the Sulforhodamine B assay. Compounds 2, 4, 5, and 6 showed high inhibition in at least two tested cell lines, while compound 3 showed low inhibition. Compound 1 exhibited over 90% inhibition in all three studied cell lines and was selected for IC50 evaluation. Compound 1 demonstrated IC50 below 9.2 µM in all three tumor cell lines, indicating excellent antitumor effects. A549 cell line was chosen for further testing with compound 1 due to the relevance of lung cancer. Hemolysis assay on human erythrocytes suggested that compound 1 is non-toxic to healthy cells, as it did not cause hemolysis at any tested concentrations. Clonogenic assay showed a significant reduction in the ability of A549 cells to form clones at all tested concentrations of compound 1, indicating inhibition of metastatic effects. Compound 1 also affected cell migration, with higher concentrations inhibiting cell migration 48 hours post-treatment. Additionally, DAPI and Phalloidin FITC staining revealed morphological changes indicative of cell death, such as reduced cytoplasmic material and altered nuclear shape, suggesting apoptosis. Annexin V and propidium iodide staining indicated a percentage of positive cells for apoptosis. The results suggest that compound 1 may have antitumor and antimetastatic effects, inducing morphological changes characteristic of apoptosis in A549 cells.